Supervisi Pendidikan Berbasis Profetik Perspektif Al-Qur’an - Roni Harsoyo (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo (previously known as IAIN Ponorogo), 2024)
Educational supervision as one form of effort in one of the functions of educational management plays a very strategic role in placing each educational program so that it remains on track in its implementation. However, the facts show that the implementation of educational supervision has not been maximized, there are still many obstacles faced so that it is ineffective and does not have a significant impact on improving the quality of education. So that a new breakthrough is needed in educational supervision that does not only focus on academic achievement, but also on the formation of a whole, characterful, and highly moral human being. Namely by implementing prophetic-based educational supervision. Through a qualitative descriptive approach in the form of a library research, this article aims to describe the prophetic values ??contained in the Qur'an that can be implemented in the educational supervision process. The results of the search found that; The prophetic values ??that can be developed in educational supervision are: 1) Supervisors in carrying out supervision must be based on monotheism, honesty, justice, wisdom and trustworthiness, provide examples, advise ma'ruf, deliberation and politeness, cooperative/cooperation, and constructive and creative; 2) The target/object of supervision must have the intention to improve themselves, be honest and not manipulate, and accept it as a form of practice.